Quality Improvement of Refuse-Derived Fuel from Landfilled Waste Using Solar Greenhouse Biodrying System - Sevina, Raisa; Widyarsana, I Made Wahyu; Wulandari, Suci (Dampak, 2024)
Final Disposal Sites (landfills) serve as the endpoint in the municipal solid waste management system, functioning as the final destination for our daily waste. Currently, Indonesia is experiencing a waste crisis due to the continuously increasing volume of waste generation, which leads to the rapid overfilling of landfill sites. One of the potential solutions for utilizing landfill waste is the production of Refuse-Derived Fuel (RDF), an alternative fuel derived from solid waste. However, waste that has been buried in landfills generally contains high moisture content, rendering it unsuitable for immediate RDF application. The calorific value of RDF depends greatly on its moisture content, with higher moisture levels resulting in lower energy output. Therefore, a pre-treatment process in the form of drying is necessary to reduce moisture content and optimize the fuel quality of RDF. This study applies the Solar Greenhouse Biodrying (SGB) method as a waste drying technology that combines heat from solar radiation with biological heat generated during aerobic degradation. This method was selected due to its suitability to Indonesia’s tropical climate and its potential for large-scale application without requiring high external energy input. The waste material used in this study was obtained from landfill waste excavated at a depth of 3 meters, with an estimated age of approximately 9 years. In this study, a mixture of fresh waste and excavated landfill waste was dried using various composition ratios: 1:0 (control), 1:1, 1:2, 1:3, and 1:4. The results show that the SGB method effectively reduced moisture content by 27–62.2% and increased the calorific value to a range of 7.5–14 MJ/kg. The waste composition ratio significantly influenced moisture reduction, with the most optimal result found at a 1:2 ratio, which provided the best balance between drying efficiency and energy enhancement. These findings indicate that the SGB method is an effective alternative for waste drying prior to further utilization as RDF. Keyword: landfill mining, solar greenhouse biodrying, refuse-derived fuel, municipal solid waste, moisture content